Effect of Glycolic Extract of Dillenia indica L. Combined With Microcurrent Stimulation on Experimental Lesions in Wistar Rats - Migliato, Ketylin F. [UNESP]; Chiosini, Mateus A. [UNESP]; Mendonca, Fernanda A. [UNESP]; Esquisatto, Marcelo A. [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Santos, Glaucia M. T. [UNESP] (H M P Communications, 2011)
This study evaluated the wound healing activity of a glycolic extract of Dillenia indica (GED) prepared from the mature fruits of the plant applied alone or in combination with microcurrent stimulation to skin wounds surgically induced on the back of Wistar rats. Methods. The animals were randomly divided into six groups: (A) negative control group; (B) group receiving microcurrent application (MC; [10 mu A/2 mins]); (C) group treated with GED; (D) group treated with an emulsion containing GED; (E) group treated with GED and MC, and (F) group treated with the emulsion containing GED and MC. Tissue samples were obtained 2, 6, and 10 days after injury and underwent structural and morphometric analysis, Results. There were observed differences in wound healing among the various treatments when compared to the control group. The combination of microcurrent plus extract or microcurrent plus emulsion containing GED was advantageous in all of the studied parameters (P < 0.05) when compared to the other groups with positive effects seen regarding newly formed tissue, number of fibroblasts, and number of newly formed blood vessels. The morphometric data confirmed the structural findings. Conclusion. Microcurrent application alone or combined with GED exerted significant effects on wound healing in this experimental model. This was probably due to the efficacy of microcurrent application since the extract alone did not significantly accelerate the healing process. D indica fruit extract most likely participates in the wound healing process as a result of its anti-inflammatory properties.